Rabbits immunized with Epstein-Barr virus gH/gL or gB recombinant proteins elicit higher serum virus neutralizing activity than gp350. Issue 34 (25th July 2016) - Cui, Xinle; Cao, Zhouhong; Chen, Quanyi; Arjunaraja, Swadhinya; Snow, Andrew L.; Snapper, Clifford M.
Highlights: There is currently no prophylactic vaccine for EBV in clinical use. EBV gp350 does not prevent EBV infection in a phase II clinical trial. EBV gH/gL and EBV gB critical for EBV entry into B cells and epithelial cells. Monomeric and trimeric EBV gH/gL and trimeric gB proteins produced in CHO cells. Vaccination with EBV gH/gL or gB elicits higher neutralization titers than gp350. Abstract: Epstein-Barr virus (EBV) is the primary cause of infectious mononucleosis and has been strongly implicated in the etiology of multiple epithelial and lymphoid cancers, such as nasopharyngeal carcinoma, gastric carcinoma, Hodgkin lymphoma, Burkitt lymphoma, non-Hodgkin lymphoma and post-transplant lymphoproliferative disorder. There is currently no licensed prophylactic vaccine for EBV. Most efforts to develop prophylactic vaccines have focused on EBV gp350, which binds to CD21/CD35 to gain entry into B cells, and is a major target of serum neutralizing antibody in EBV seropositive humans. However, a recombinant monomeric gp350 protein failed to prevent EBV infection in a phase II clinical trial. Thus, alternative or additional target antigens may be necessary for a successful prophylactic vaccine. EBV gH/gL and gB proteins coordinately mediate EBV fusion and entry into B cells and epithelial cells, strongly suggesting that vaccination with these proteins might elicit antibodies that will prevent EBV infection. We produced recombinant trimeric and monomeric EBV gH/gL heterodimeric proteins and a trimeric EBV gB protein, in addition to tetrameric and monomeric gp350 1–470 proteins, in Chinese hamster ovary cells. We demonstrated that vaccination of rabbits with trimeric and monomeric gH/gL, trimeric gB, and tetrameric gp350 1–470 induced serum EBV-neutralizing titers, using cultured human B cells, that were >100-fold, 20-fold, 18-fold, and 4-fold higher, respectively, than monomeric gp350 1–470 . These data strongly suggest a role for testing EBV gH/gL and EBV gB in a future prophylactic vaccine to prevent EBV infection of B cells, as well as epithelial cells.